Selection of cowpea populations tolerant to water deficit by selection index - Rodrigues, Erina; Damasceno-Silva, Kaesel; Rocha, Maurisrael; Bastos, Edson; Teodoro, Paulo (Revista Ciência Agronômica, 2017)
The objective of this work was to use different selection criteria to identify cowpea genotypes tolerant to water deficit to be used in recurrent selection programs aiming to reduce the cowpea crop cycle and improve its productive components. Six cowpea genotypes were crossed in a complete diallel scheme. The experiment was conducted in an incomplete block experimental design in a triple lattice arrangement, with the 30 F2 populations of cowpea. The genetic variability of 10 traits was verified, and the following selection criteria were used: direct and indirect selection, classical index, index based on desired gains, and index based on sum of ranks. The number of days to flowering (NDF), number of days to maturity (NDMD), pod weight (PW), grain weight per pod (GWP) and 100-grain weight (100GW) were classified as primary traits, and the others as secondary. The direct selection based on the pod weight was the most efficient criterion to reduce the crop cycle and improve productive components of the cowpea genotypes subjected to water deficit conditions. The genotypes Pingo-de-Ouro-1-2 × MNC99-510F-16-1, CNCx698-128G × MNC99-510F-16-1, MNC99-510F-16-1 × Pingo-de-Ouro-1-2, Pingo-de-Ouro-1-2 × BRS Paraguaçu, Santo-Inácio × Pingo-de-Ouro-1-2, BRS Xiquexique × Pingo-de-Ouro-1-2 and Pingo-de-Ouro-1-2 × Santo-Inácio were the most suitable to be used in interpopulation recurrent selection programs aiming to reduce the crop cycle and improve productive components of cowpea grown under water deficit conditions.